Midwives in the United Europe - Iwanowicz-Palus, Grażyna; Bień, Agnieszka; Golonka, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2013)
The midwife is a person who after the formal acceptance into the program of study in the field of obstetrics approved by authorities of the Member State of the European Union, successfully completed a series of vocational training in midwifery and has received appropriate qualifications, making her eligible to register obstetric practice and/or providing the right to exercise profession. Within the European Union the issue of access to practice as a midwife is subject to harmonization in range that is necessary for the free flow of persons and services within the common market pursuant to the provisions of the Treaty establishing the European Community. For professionals this system means full freedom of movement between member states, freedom to practice a profession or to undertake activities. Nursing Topics 2013; 21 (1): 117–122